Inhibition of Golgi Apparatus Glycosylation Causes Endoplasmic Reticulum Stress and Decreased Protein Synthesis - Xu, Yu-Xin (American Society for Biochemistry and Molecular Biology, 2010)
Nucleotide sugar transporters of the Golgi apparatus play an essential role in the glycosylation of proteins, lipids, and proteoglycans. Down-regulation of expression of the transporters for CMP-sialic acid, GDP-fucose, or both unexpectedly resulted in accumulation of glycoconjugates in the Golgi apparatus rather than in the plasma membrane. Pulse-chase experiments with radiolabeled sugars and amino acids showed decreased synthesis and secretion of both nonglycoproteins and glycoproteins. Further studies revealed that the above silencing induced endoplasmic reticulum stress and inhibited protein translation initiation. Together these results suggest that global inhibition of Golgi apparatus glycosylation may lead to important secondary metabolic changes, unrelated to glycosylation.